FRI0573-HPR Effects of Relaxation Techniques in Total Knee Arthroplasty Patients during Their Hospital Stay. (10th June 2014) - Guney, H.; Vardar Yagli, N.; Caglar, O.; Yuksel, I.
Abstract : Background: Surgical techniques and treatment methods of the arthroplasty have been improved and the results after total knee arthroplasty (TKA) are generally good. However, some patients have suboptimal postoperative results with respect to pain and physical functioning and may not be satisfied with the results of their TKA. Psychological symptoms were found to be associated with these suboptimal results. Objectives: To determine weather relaxation techniques had beneficial effects on pain, sleeping quality, functional status and physiological symptoms in TKA patients during their hospital stay. Methods: Forty-seven patients who underwent unilateral TKA were randomized as relaxation techniques (RT) group (n=24) and control group (n=23). RT group was received physiotherapy treatment and 8 sessions (2 times a day, for four days after surgery) of relaxation exercises. Control group received only physiotherapy treatment. Intensity of pain and quality of sleeping were measured with visual analog scale (VAS). Early functional levels were assessed with the Iowa Level of Assistance Scale (ILAS). The measurements were done first four days after surgery. Depression and anxiety levels were detected with the use of Hospital Anxiety and Depression scale (HADS). Repeated measurements of ANOVA were used to analyze differences between groups for pain, ILAS and quality of sleeping. Student t test was used to analyze depression and anxiety levels between groups. Results: The difference in sleeping quality results were significant between RT group and control group (F(3, 135) =6.539, p=0.001). Sleeping quality results were better in RT group compared to control group in postoperative day 1 (p<0.001), day 2 (p<0.001) and day 3 (p<0.001). On postoperative day four there was no difference in sleeping quality between groups (p=0.062). HADS depression (p=0.002) and HADS anxiety (p=0.014) scores were lower in RT group compared to control group. There were no differences in pain levels (F(3, 135) =0.988, p=0.401) and in ILAS scores (F(3, 135) =2.234, p=0.076) between groups. Conclusions: Relaxation techniques can be applied to TKA patients during their hospital stay. RT enhances sleeping quality and lessens depression and anxiety symptoms in TKA patients. References: Duivenvoorden T, Vissers MM, Verhaar JA, Busschbach JJ, Gosens T, Bloem RM, Bierma-Zeinstra SM, Reijman M. Anxiety and depressive symptoms before and after total hip and knee arthroplasty: a prospective multicentre study. Osteoarthritis Cartilage. 2013 Dec;21(12):1834-40. Taibi DM, Vitiello MV. Yoga for osteoarthritis: nursing and research considerations. J Gerontol Nurs. 2012 Jul;38(7):26-35 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4381